Francisco Garro: O magnum mysterium - Henriques, Luís (2021)
Edition of the motet "O magnum mysterium", for six voices, by the Spanish composer Francisco Garro (c.1556-c.1623). Garro was active in Lisbon as master of the Portuguese Royal Chapel from 1592 to 1623, and this motet was published in one of his 1609 collection of masses, printed in Lisbon at the Pedro Craesbeeck workshop.